Cooperativity of CD44 and CD49d in leukemia cell homing, migration, and survival offers a means for therapeutic attack - Singh, Vibuthi; Erb, Ulrike; Zöller, Margot (The journal of immunology, 2013)
A CD44 blockade drives leukemic cells into differentiation and apoptosis by dislodging from the osteogenic niche. Because anti-CD49d also supports hematopoietic stem cell mobilization, we sought to determine the therapeutic efficacy of a joint CD49d/CD44 blockade. To unravel the underlying mechanism, the CD49d− EL4 lymphoma was transfected with CD49d or point-mutated CD49d, prohibiting phosphorylation and FAK binding; additionally, a CD44− Jurkat subline was transfected with murine CD44, CD44 with a point mutation in the ezrin binding site, or with cytoplasmic tail-truncated CD44. Parental and transfected EL4 and Jurkat cells were evaluated for adhesion, migration, and apoptosis susceptibility in vitro and in vivo. Ligand-binding and Ab-blocking studies revealed CD44-CD49d cooperation in vitro and in vivo in adhesion, migration, and apoptosis resistance. The cooperation depends on ligand-induced proximity such that both CD44 and CD49d get access to src, FAK, and paxillin and via lck to the MAPK pathway, with the latter also supporting antiapoptotic molecule liberation. Accordingly, synergisms were only seen in leukemia cells expressing wild-type CD44 and CD49d. Anti-CD44 together with anti-CD49d efficiently dislodged EL4-CD49d/Jurkat-CD44 in bone marrow and spleen. Dislodging was accompanied by increased apoptosis susceptibility that strengthened low-dose chemotherapy, the combined treatment most strongly interfering with metastatic settlement and being partly curative. Ab treatment also promoted NK and Ab-dependent cellular cytotoxicity activation, which affected leukemia cells independent of CD44/CD49d tail mutations. Thus, mostly owing to a blockade of joint signaling, anti-CD44 and anti-CD49d hamper leukemic cell settlement and break apoptosis resistance, which strongly supports low-dose chemotherapy.
Published online November 1, 2013
Gesehen am 03.02.2022